Proceedings of the 4th International Workshop on Genetic Improvement Workshop 2018
DOI: 10.1145/3194810.3194813
|View full text |Cite
|
Sign up to set email alerts
|

Experiments in genetic divergence for emergent systems

Abstract: Emergent software systems take a step towards tackling the everincreasing complexity of modern software, by having systems selfassemble from a library of building blocks, and then continually re-assemble themselves from alternative building blocks to learn which compositions of behaviour work best in each deployment environment. One of the key challenges in emergent systems is populating the library of building blocks, and particularly a set of alternative implementations of particular building blocks, which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…The second research direction is to consider additional computational problems associated with emergent software systems. Of particular interest here is the automated synthesis of both variants of existing components and new components from input-output examples [47,48]. Analyses of these problems may also give insights into the more general problem of program synthesis [49,50,51] Observe that interfaces base, vertStatJ for 1 ≤ J ≤ |V |, and domSetStat and components VertexStatusJ for 1 ≤ J ≤ |V |, DomSetStatus0, and DomSetStatus1 are the same as in the reduction in the proof of Result A.9.…”
Section: Discussionmentioning
confidence: 99%
“…The second research direction is to consider additional computational problems associated with emergent software systems. Of particular interest here is the automated synthesis of both variants of existing components and new components from input-output examples [47,48]. Analyses of these problems may also give insights into the more general problem of program synthesis [49,50,51] Observe that interfaces base, vertStatJ for 1 ≤ J ≤ |V |, and domSetStat and components VertexStatusJ for 1 ≤ J ≤ |V |, DomSetStatus0, and DomSetStatus1 are the same as in the reduction in the proof of Result A.9.…”
Section: Discussionmentioning
confidence: 99%
“…The offline code synthesiser, however, is the novel part of the proposed framework. Inspired by recent advances in code synthesis with techniques ranging from genetic improvement [4] to neural networks [5], we envision the code synthesiser as a key element to advance self-improving systems' state-of-the-art.…”
Section: Approachmentioning
confidence: 99%
“…Depending on the component, different code synthesis strategies should be applied. For example, for components that are generated from improving existing components, such as cache components, which are generated by improving their hash function, techniques such as genetic improvement has been shown effective [4], whereas the synthesis of entirely new components may use neural networks as described in [5].…”
Section: Approachmentioning
confidence: 99%
“…These systems rely on the existence of variation in their pool of building blocks to learn better compositions of behaviour -such as different sorting algorithms, cache replacement algorithms, or load balancing policies. While most systems require human engineers to generate this pool of variation, an initial study by McGowan et al indicated that genetic improvement (GI) could automate the generation of environment-tailored variation with the example of a hash table [3]. Based on this study, we examine the wider set of challenges in genetic improvement for emergent systems and some of the most promising research directions to explore.…”
Section: Introductionmentioning
confidence: 98%
“…b) Generalisation: While optimisation to a given target is important, genetic improvement algorithms typically aim towards a fixed environment -for example optimising a particular component towards a specific set of inputs. Rather than using GI to derive a hash function for all words in the English language, we would instead use a smaller subset of commonly-seen inputs from a particular environment [3]. However, this presents a potential dichotomy between spe-[pre-print version for personal use] Appears at IEEE GI 2021 cialising on a smaller set of inputs or generalising on a much broader set -a problem analogous to over-fitting in wider machine learning and a significant problem in all evolutionary systems.…”
Section: Introductionmentioning
confidence: 99%